Behavioural economics and economic behaviour in classical Athens - Lewis, David (Edinburgh University Press, 2018)
This article addresses the formalist-substantivist controversy in ancient economic history by bringing two new approaches to bear on it. On the one hand, it critiques the formalist approach (which relies on assumptions about economically rational behaviour) by examining critiques of neo-classical economics from the behaviouralist school. This shows that even modern economic actors are constrained in their capacity for rational behaviour by cognitive and emotional factors; a fortiori, we cannot expect Olympian rationality in antiquity. On the substantivist side, it reaffirms the importance of embeddedness, but uses Granovetter's view of embeddeness instead of Polanyi's. It also critiques the Finleyan reading of social values in ancient Greece that allegedly prevented economic growth and profit-oriented behaviour.